2020
DOI: 10.1002/cmdc.202000248
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Profile and Molecular Modeling of Cyclic Opioid Analogues Incorporating Various Phenylalanine Derivatives

Abstract: Peptide‐based agonists of the μ opioid receptor (μOR) are promising therapeutic candidates for pain relief with reduced side effects compared to morphine. A deep understanding of μOR–ligand interactions is necessary for future design of peptide‐based opioid analgesics. To explore the requirements of the μOR binding pocket, eight new analogues of our cyclic peptide Tyr‐c[d‐Lys−Phe−Phe−Asp]NH2 displaying high μOR affinity were synthesized, in which Phe in either the third or fourth position was replaced by vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Similar binding poses were also proposed based on molecular modelling results for the opioid fragment of other opioid/antitachykinin hybrids [ 17 ] or some Tyr- d -Ala-Phe-Phe (TAPP) derivatives [ 66 ]. Aromatic rings of BU72 (experiment [ 67 ]), fentanyl (modelling [ 68 ]) cyclic opioid derivatives (modelling [ 69 ]), or linear peptide opioids (modelling [ 70 ]) were found to be located similarly as the Phe 4 ring in MOR-1 pose. For the -NH-NH-Z- d -Trp fragment, a few quite distinct binding poses are found at MOR.…”
Section: Resultsmentioning
confidence: 99%
“…Similar binding poses were also proposed based on molecular modelling results for the opioid fragment of other opioid/antitachykinin hybrids [ 17 ] or some Tyr- d -Ala-Phe-Phe (TAPP) derivatives [ 66 ]. Aromatic rings of BU72 (experiment [ 67 ]), fentanyl (modelling [ 68 ]) cyclic opioid derivatives (modelling [ 69 ]), or linear peptide opioids (modelling [ 70 ]) were found to be located similarly as the Phe 4 ring in MOR-1 pose. For the -NH-NH-Z- d -Trp fragment, a few quite distinct binding poses are found at MOR.…”
Section: Resultsmentioning
confidence: 99%
“…β-Peptides (made of only β-amino acids) in general do not appear in nature, though among the opioid peptides, there are examples of such synthetic analogs [ 27 ]. More often mixed α/β-peptides, in which one or more β-residues are incorporated instead of some α-amino acids, were constructed [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our former work [ 33 ], we devised an interaction model for RP-170 and its analogs, in which the peptides were anchored in the MOR binding pocket by interactions at the three key binding subsites. According to that model, in the S1 subsite, the protonable amino group of Tyr 1 interacts with Asp 147 (a typical contact for high-affinity MOR agonists of both peptide [ 24 ] and non-peptide character [ 38 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Position 2 of EM has been modified successfully without damaging the affinity but improving the enzymatic hydrolysis resistance despite the reduction of MOR selectivity over DOR [ 111 , 136 , 142 , 240 , 259 ]. Likewise, many studies showed that the substitutions of various β-amino acids including acyclic β-amino acids into EMs were well tolerated at position 2, unlike the other positions [ 136 , 141 , 143 ].…”
Section: Peptidomimetics For Opioid Receptorsmentioning
confidence: 99%